FTIR Analysis of Nanoparticle-Doped Polymer Dispersed Cholesteric Liquid Crystals - Gajghate, Vishakha (Journal of Research Updates in Polymer Science, 2025)
This study investigates the structural and chemical interactions in nanoparticle-doped polymer dispersed cholesteric liquid crystals using Fourier Transform Infrared (FTIR) spectroscopy. Cholesteric liquid crystals known for their helical structure and optical selectivity, were embedded in a polymer matrix, and doped with silver metal nanoparticles. Samples were fabricated using polymerization-induced phase separation and analyzed through FTIR to examine the addition of nanoparticles and their influence on functional group behavior. Shifts in characteristic absorption bands (C=O, O–H, and metal–oxygen) and appearance of new peaks in the fingerprint region suggested significant interfacial interactions among the nanoparticles and the composite matrix. The findings reveal the effectiveness of FTIR in elucidating the molecular-level effects of nanoparticle doping in liquid crystal-based hybrid systems. Such improvements underscore the significance of nanoparticle–polymer interactions in designing thermally robust functional composites, thereby expanding their potential for advanced structural, optical, and sensing applications.